Does organized atrial tachycardia after a pulmonary vein isolation-only procedure portend better outcome of repeat ablation compared to recurrent atrial fibrillation? - Riesz Tamás János; Bencsik Gábor; Sághy László; Pap Róbert (2025)
Better outcome has been suggested for repeat procedures after atrial fibrillation (AF) ablation, when recurrence presented as organized atrial tachycardia (OAT) compared to recurrent AF. However, this contradicts the finding of more advanced atrial remodeling in patients with OAT recurrence and may be related to iatrogenesis by substrate modification during the index procedure. Therefore, we examined the prognostic significance of the type of recurrent arrhythmia after pulmonary vein isolation (PVI) without additional substrate modification.We included 185 patients (88 female, 64 ± 9 years) undergoing repeat ablation after index PVI for recurrent OAT (24%) or AF (76%). The recurrence rate, arrhythmia-free survival time, and the type of further recurrences were recorded.There was no difference in the rate and mean time of arrhythmia-free survival between patients with OAT versus AF recurrence after the first (49% vs. 52%, p = .72 and 51.08 ± 6.66 vs. 53.37 ± 4.75 months, p = .54, respectively) and last (60% vs. 58%, p = .80 and 63.2 ± 7.04 vs. 61.2 ± 5.32 months, p = .23, respectively) redo procedure. AF occurred in the majority of subsequently recurring patients in both groups. No significant difference was found in the outcome of redo procedures between patients with typical flutter and atypical OAT, but a higher rate of successful rhythm control was observed in those with paroxysmal, as compared to persistent AF recurrence.After a PVI-only index procedure, recurrent OAT is not associated with a better outcome of redo procedures compared to recurrent AF. After repeat ablations, both groups experience AF as the dominant further recurrence.
Keywords: Klinikai orvostan